Role of the V1G1 subunit of V-ATPase in breast cancer cell migration - Maria De Luca (Nature Portfolio, 2021)
Abstract V-ATPase is a large multi-subunit complex that regulates acidity of intracellular compartments and of extracellular environment. V-ATPase consists of several subunits that drive specific regulatory mechanisms. The V1G1 subunit, a component of the peripheral stalk of the pump, controls localization and activation of the pump on late endosomes and lysosomes by interacting with RILP and RAB7. Deregulation of some subunits of the pump has been related to tumor invasion and metastasis formation in breast cancer. We observed a decrease of V1G1 and RAB7 in highly invasive breast cancer cells, suggesting a key role of these proteins in controlling cancer progression. Moreover, in MDA-MB-231 cells, modulation of V1G1 affected cell migration and matrix metalloproteinase activation in vitro, processes important for tumor formation and dissemination. In these cells, characterized by high expression of EGFR, we demonstrated that V1G1 modulates EGFR stability and the EGFR downstream signaling pathways that control several factors required for cell motility, among which RAC1 and cofilin. In addition, we showed a key role of V1G1 in the biogenesis of endosomes and lysosomes. Altogether, our data describe a new molecular mechanism, controlled by V1G1, required for cell motility and that promotes breast cancer tumorigenesis.